Genomic and phenotypic characterization of 26 novel marine bacterial strains with relevant biogeochemical roles and widespread presence across the global ocean - Rey-Velasco, Xavier; Lucena, Teresa; Belda, Ana; Gasol, Josep M.; Sánchez, Olga; Arahal, David R.; Pujalte, María J. (Frontiers in Microbiology, 2024)
Prokaryotes dominate global oceans and shape biogeochemical cycles, yet most taxa remain uncultured and uncharacterized as of today. Here we present the characterization of 26 novel marine bacterial strains from a large isolate collection obtained from Blanes Bay (NW Mediterranean) microcosm experiments made in the four seasons. Morphological, cultural, biochemical, physiological, nutritional, genomic and phylogenomic analyses were used to characterize and phylogenetically place the novel isolates. The strains represent 23 novel bacterial species and 6 novel genera: three novel species pertaining to class Alphaproteobacteria (families Rhodobacteraceae and Sphingomonadaceae), six novel species and three new genera from class Gammaproteobacteria (families Algiphilaceae, Salinispheraceae and Alteromonadaceae), thirteen novel species and three novel genera from class Bacteroidia (family Flavobacteriaceae) and one new species from class Rhodothermia (family Rubricoccaceae). The bacteria described here have potentially relevant roles in the cycles of carbon (e.g. carbon fixation or energy production via proteorhodopsin), nitrogen (e.g. denitrification or use of urea), sulfur (oxidation of sulphur compounds), phosphorus (acquisition and use of different forms of phosphorus and remodeling of membrane phospholipids) and hydrogen (oxidation of hydrogen to obtain energy). We mapped the genomes of the presented strains to the Tara Oceans metagenomes to unveil that these strains were globally distributed, with those of family Flavobacteriaceae being the most widespread and abundant, while Rhodothermia being the rarest and most localized. While molecular-only approaches are also important, our work stresses the importance of culturing as a powerful tool to further understand the functioning of marine bacterial communities.